Empirical Approach in Learning Creed and Quranic Stories: An Attempt to Internalize the Values Therein - Gilang Dzaky Mubarak; Nasikhin Nasikhin; Mustopa Mustopa (LP3M KH Yazid Karimullah Institute, 2025)
This study aims to examine the implementation of an empirical approach in learning aqidah based on Qur'anic stories as a strategy for internalizing values in adolescents. The background of this study is based on the urgent need to present contextual aqidah education, touching on the affective and spiritual aspects of students, and relevant to the challenges of today's adolescent life. Using a descriptive qualitative method, this study involved five main informants consisting of teachers and students in an Islamic educational environment. Data were collected through in-depth interviews, observations, and then analyzed using a thematic approach. The results of the study indicate that an empirical approach in learning aqidah, which emphasizes direct experience, value reflection, and strengthening students' emotional involvement through Qur'anic stories, has proven effective in shaping character and increasing adolescent spiritual awareness. The forms of its application include dramatization of the prophet's story, social projects, environmental observation, value discussions, and self-reflection. The main supporting factors in the implementation of this approach include teacher creativity, student openness, institutional support, and the integration of Qur'anic values into school culture. The obstacles faced include time constraints, lack of teacher training, and the dominance of cognitive approaches in the curriculum. This study concludes that an empirical approach based on Qur'anic stories is a strategic alternative for down-to-earth and transformative aqidah education. The implications of this study recommend the development of a sustainable and collaborative learning model to support the formation of a generation of believers, morals, and Qur'anic insight.